2007
DOI: 10.18553/jmcp.2007.13.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Multiple Medication Use Among TRICARE Beneficiaries Aged 65 Years and Older

Abstract: he simultaneous use of multiple prescription medications has been repeatedly identified as an area of concern, particularly among our nation' s older adults.1 While older adults typically require more medications to manage multiple comorbidities, disease-centric prescribing, reduced organ function, and higher use of over-the-counter products among older adults complicates a prescriber' s or pharmacist' s ability to anticipate how concomitant use of multiple medications is likely to affect the underlying mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
(24 reference statements)
2
13
0
3
Order By: Relevance
“…Cardiovascular, central nervous system, and alimentary tract drugs were the top three medication classes most often prescribed for the elderly in previous studies 11–18, 33. Our study gave similar results except for central nervous system drugs.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Cardiovascular, central nervous system, and alimentary tract drugs were the top three medication classes most often prescribed for the elderly in previous studies 11–18, 33. Our study gave similar results except for central nervous system drugs.…”
Section: Discussionsupporting
confidence: 85%
“…The aging of the population and the resulting increase of multiple chronic diseases have led to rising drug prescription 1–7. Although many studies have also recently described the high use of medications in community‐dwelling elderly people,8–13 only few have analyzed the associations of chronic medications and number of drug prescriptions with age and sex 14–17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As civilian and government hospitals do not have combined medical records, it is difficult for the DoD to properly manage medications. In one study of 123,682 TRICARE beneficiaries 65 years and older, 50% obtained six or more medications, and 3% obtained 16 or more medications from the pharmacy during a 90-day period (Linton, Garber, Fagan, & Peterson, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…A prior study on the age 65+ TRICARE beneficiary population found that maintenance medications dominated the medication lists of TRICARE beneficiaries, and treatments for cardiovascular disease, high blood pressure, diabetes, and arthritis topped the list of most commonly used medications. 18 These beneficiaries represent the ideal target population for DoD' s migration initiative for the transfer of prescription fills from community and military pharmacies to TMOP.…”
mentioning
confidence: 99%